Surface water conditions and calcium carbonate preservation in the Fram Strait during marine isotope stage 2, 28.8–15.4 kyr - Zamelczyk, Katarzyna; Rasmussen, Tine Lander; Husum, Katrine; Godtliebsen, Fred; Hald, Morten (Paleoceanography, 2014)
Source at http://doi.org/10.1002/2012PA002448 We present a high-resolution record of calcium carbonate preservation alongside the distribution pattern of planktic foraminifera from the Fram Strait. The record covers the marine isotope stage (MIS) 2, 28.8 to 15.4 kyr, including the Last Glacial Maximum (LGM) and the early deglaciation in multidecadal temporal resolution. The investigation is based on the distribution patterns of planktic foraminifera, stable isotopes, mean shell weight of Neogloboquadrina pachyderma, the degree of fragmentation of planktic shells, CaCO 3 content, and geochemical and sedimentological data. The dissolution proxies indicate long-lasting periods of markedly reduced preservation of calcium carbonate at ~28.8–27.2, ~24.1–23.2, and ~16.6–15.4 kyr in addition to a number of short-lasting periods (< 300 year) during the LGM. These periods are accompanied by a simultaneous and significant reduction in specimens of subpolar planktic foraminifera indicating a southward expansion of Arctic surface water masses. Prolonged periods with high abundances of subpolar foraminiferal species and good preservation of calcium carbonate are attributed to increased influence of Atlantic water masses, which appears to persist throughout most of the MIS 2. Comparison to Holocene (MIS 1) shell weight records shows that the preservation during MIS 2 was overall better, even during the events of dissolution. This was probably a reflection of the low concentration of atmospheric CO 2 at the time.